2020
DOI: 10.1116/6.0000408
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering study of nanoscale Mo/Si and Mo/Be periodic multilayer structures

Abstract: Investigation of the microstructure and phase analysis of the periodic Mo/Si and Mo/Be multilayers are essential for depositing high reflective multilayers that operate at soft x-ray to extreme ultraviolet radiations. Raman spectroscopy revealed the presence of an amorphous phase of silicon (Si) in the Mo/Si multilayers. Furthermore, the disorder of the amorphous Si phase was increased with decreasing the periodic thickness of the Si layers in the nanoscale Mo/Si multilayers. The polycrystalline Mo periodic la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This coupling may induce a possible effect on phonon excitation using Raman scattering. The E 2g mode of Be nanolayers in the Mo/Be multilayers became broader, and it is red-shifted compared to crystalline bulk Be . Such a modification of the E 2g mode in the Be nanolayers is associated with stretching of Be–Be bonding due to defects, surface bonds, and formation of dimers .…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…This coupling may induce a possible effect on phonon excitation using Raman scattering. The E 2g mode of Be nanolayers in the Mo/Be multilayers became broader, and it is red-shifted compared to crystalline bulk Be . Such a modification of the E 2g mode in the Be nanolayers is associated with stretching of Be–Be bonding due to defects, surface bonds, and formation of dimers .…”
Section: Introductionmentioning
confidence: 92%
“…Recently, Raman scattering showed that Be nanospacer layers in the Mo/Be multilayer were condensed into the crystalline structure. 13 At normal temperature and pressure, the bulk Be existing in hexagonal close-packed (hcp) lattice, which has two atoms per unit cell with a 0 = 0.22866 nm and c 0 = 0.35833 nm, 15 located at D 3h symmetry. The six normal modes of zero wavevectors belong to the irreducible representations of A 2u + B 1g + E 1u + E 2g modes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations